Caracterización metrológica de las básculas utilizadas en el proceso de galvanizado en la empresa SUSEINCO SAS y desarrollo de un software para su validación in situ (2021)
The project was carried out due to the requirement of the SUSEINCO company in the galvanizing area, where they presented uncertainty problems with the weight measurements obtained from the scale. For this reason, an instrument calibration process was designed and implemented using statistical techniques - least squares method -, data collection and comparison processes to verify that reliable measurement values are obtained with the minimum degree of uncertainty. In order to obtain a metrological assurance, a process of data collection of the measurements, calibration techniques and comparison of results was carried out, through the coefficient F which indicates the level of certainty of the sample and through which the makes the decision whether to accept or reject the results.